The problem of torture practice in criminal investigation in Kazakhstan - Bramontov, R.S. (Mediterranean Journal of Social Sciences Vol.5, No. 23, 639-644, 2014)
The article investigates the problem of systematic application of torture in criminal investigation in Kazakhstan. Modern methods of torture most often used by police officers are described. Special focus is given to the identification of causes fostering torture practice in crime investigation as well as its prevention
Keywords: torture, crime investigation, torture methods, causes of torture practice, torture prevention